The construction and analysis of repeated measurement designs (RMD) using the trial and error method - Shakeel A. Mir; Immad A. Shah (Statistics in Transition New Series, 2021)
Repeated measurement designs prove broadly applicable in almost all branches of biosciences, including agriculture, animal husbandry, botany, zoology. Unbiased estimators for elementary contrasts among direct and residual effects are obtainable in this class of designs, which is considered their important property. In this paper, an attempt was made to provide a new method of overcoming a drawback in the construction method developed by Afsarinejad (1983), where one or more treatments may occur more than once in certain sequences causing the constructed designs to no longer remain uniform in the examined periods. Nine designs were constructed and presented jointly with their corresponding mathematical analyses.
Keywords: 519; residual effects; order effects; balanced minimal RMD